Genetics in the X-Men film franchise: mutants as allegories of difference - Grimsted, Sonora R.; Krizner, Katerina G.; Porter, Cynthia D.; Clayton, Jay (Frontiers in Genetics, 2024)
This article analyzes the complete corpus of live-action X-Men movies for their depictions of genetics and otherness. The researchers watched and qualitatively coded all thirteen movies produced by 20 th Century Fox that take place in the same shared cinematic universe, beginning with X-Men (2000) and ending with The New Mutants (2020). The X-Men movies are unusual summer blockbusters since they explore genetic topics through their central characters, mutants, who are genetically different from their non-mutant peers. Mutants in the films evoke a plurality of analogies, such as mutant-as-Black and mutant-as-queer. These intersecting metaphors build upon a core of genetic difference to create a versatile but limited picture of prejudice, solidarity, and otherness.